#MeToo in Sweden: Museum Collections, Digital Archiving and Hashtag Visuality. Issue 5 (19th October 2020) - Uimonen, Paula
ABSTRACT: In October 2017, the Nordic Museum in Stockholm launched its #metoo collection. The aim was to capture the viral #MeToo campaign that in Sweden has been likened to a (feminist) revolution. Based on archival research, interviews and media analysis, this article explores public submissions to the #metoo collection and analyses the museum's rationale for collecting what is considered to be difficult cultural heritage. Noting the absence of images in the collection, the article argues that the iconic hashtag #MeToo constitutes an alternative form of digital visuality, here termed hashtag visuality. Hashtag visuality, the article suggests, is an emerging form of visual representation that captures the multimodal logic of social media, blurring distinctions between texts and images. In Sweden, #MeToo hashtag visuality reveals the contradictory prevalence of structural sexism and sexual violence in a country with a national self-image of gender equality and a self-proclaimed feminist government, while affirming feminist agency.